1982
DOI: 10.1111/j.1476-5381.1982.tb09331.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECTS OF pH ON THE AFFINITY OF PIRENZEPINE FOR MUSCARINIC RECEPTORS IN THE GUINEA‐PIG ILEUM AND RAT FUNDUS STRIP

Abstract: 1 Dose-ratios obtained with pirenzepine on the guinea-pig ileum at 30°C are indistinguishable from those obtained at 37°C.2 In 0.1 M NaCl at 37°C the pKa of pirenzepine for the loss of its last ionizable proton is 8.2. The ionization of pirenzepine is therefore markedly affected by changes in pH in the physiological range. 3 In experiments with pirenzepine on guinea-pig ileum and rat fundus made over a range of pH, the dose-ratio increases with the proportion of the protonated form present. As expected, the sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1984
1984
1996
1996

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…If the affinity of Pz binding is not determined by the state of the mAChR-N protein interaction, it follows that the membrane constraint released on dissolution with digitonin is a more general microenvironmental one, as might be provided, for instance, by the presence of a high concentration of charged groups in the vicinity of the receptor which could affect the ionization state of Pz and/or the receptor (Barlow & Chan, 1982). In this regard, it is interesting that the quaternary methiodide of Pz has a KD ofca.…”
Section: Discussionmentioning
confidence: 99%
“…If the affinity of Pz binding is not determined by the state of the mAChR-N protein interaction, it follows that the membrane constraint released on dissolution with digitonin is a more general microenvironmental one, as might be provided, for instance, by the presence of a high concentration of charged groups in the vicinity of the receptor which could affect the ionization state of Pz and/or the receptor (Barlow & Chan, 1982). In this regard, it is interesting that the quaternary methiodide of Pz has a KD ofca.…”
Section: Discussionmentioning
confidence: 99%
“…The identification and classification of multiple muscarinic receptors in central and peripheral nervous systems has been the object of several investigations using different procedures (for reviews see, Turbanti et al, 1982;Caulfield & Straugham, 1983). Recently, it was reported that pirenzepine, a 'nonclassical' muscarinic antagonist, discriminates between subtypes of muscarinic receptor; that is, in both functional and binding experiments, pirenzepine was found to have a higher affinity for muscarinic receptors of certain brain areas (see reviews by Hammer & Giachetti, 1982;Birdsall & Hulme, 1983) and of sympathetic ganglia (Brown et al, 1980) than for the muscarinic receptors in the isolated ileum or heart (Brown et al, 1980;Fuder et al, 1982;Barlow & Chan, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Hammer et al (1980) with a lower affinity for pirenzepine are of the M2 subtype (Hammer & Giachetti, 1982). Based on the selectivity for pirenzepine, the muscarinic receptors in the sympathetic ganglia are classified as the M, subtype (Brown et al, 1980), while those in ileal smooth muscle and the heart are ofthe M2 subtype (Brown et al, 1980;Fuder et al, 1982;Barlow & Chan, 1982). In the guinea-pig enteric nervous system, activation of M,-and M2-receptors produces postsynaptic depolarization and presynaptic inhibition of transmitter release, respectively (North et al, 1985).…”
Section: Introductionmentioning
confidence: 99%